Teachers engaged in research : inquiry into mathematics classrooms, grades 9-12 - Van Zoest, Laura R. (Teachers engaged in research., 2006)
This book provides examples of the ways in which 9-12 grade mathematics teachers from across North America are engaging in research. It offers a glimpse of the questions that capture the attention of teachers, the methodologies that they use to gather data, and the ways in which they make sense of what they find. The focus of these teachers' investigations into mathematics classrooms ranges from students' understanding of content to pedagogical changes to social issues. Underlying the chapters is the common goal of enabling students to develop a deep understanding of the mathematics they learn in their classrooms.